Marina Abramovic Class : fresh air. - Abramović, Marina; Bekuhrs, Annerose; Giesel, Vera; Glasmeier, Michael; Pejic, Bojana; Schwarz, Michael; Exhibition. Marina Abramovic Class : fresh air. Hochschule für Bildende Künste Braunschweig. 1999-09-17. 1999-09-26. Beitrag des Landes Niedersachsen zu Weimar 1999 - Kulturstadt Europas (Köln : Salon Verlag & Edition Köln, 1999)
This book is a collection of works from twenty three students who studied in my class at Braunschweig school of art in the period from 1997 to 1998. They deal with individual subjects which are subjective only in the fluid context of contemporarity and their different positions are inspired by reflections and experience they live in. As the title of the book suggests fresh air is a book about fresh air and a new generation of artists. It contains texts by Bojana Pejic and Michael Glasmeier. It is multilingual.
Abramovic, Marina ; Gollwitzer, Anna ; Klinker, Barbara ; Suryodarmo-Lutz, Melati ; Hanisch, Annette ; Mahler, Hannes Malte ; Begemann, Frank ; Jaffrennou, Julie ; Korbel, Maurice ; Petersen, Kristian ; Frau Müller ; Selke, Iris ; Fischer, Anke ; Chiharu Shiota ; Werner, Frank ; Herbel, Katrin ; Braun, Sarah ; Ertl, Uli ; Krumpl, Franz Gerald ; Blomeier, Oliver ; Hutter, Ruth ; Winterling, Susanne ; Monophon ; Gresser, Isabella ; Mundet Palli, Llúcia
biog. [10 p.]
Duits
Engels
boek
Keywords: Abramovic, Marina